Marjinalisasi Petani atas Nama Pemberdayaan: Problematika Mengubah Paradigma Kebijakan - Susetiawan, - (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2007)
The notion of paradigmatic change lus been widely oversimplified. Thc closes look at policy-making process on water resources issue reveals that the change is culturally-bound, within which conflicts of interest take place. Unless the image of the normality is thoroughly scrutinized and altered by the public, paradigmatic change would unlikely to take place.